Isolation of active compounds from aerial parts of Albizia Procera - S. Sivakrishnan (Journal of Global Pharma Technology, 2019)
The purpose of the study is to isolate active compounds from herbal plants that have various effects on living systems. The plants are indispensable sources for both preventive and curative medicinal preparations of various traditional medicine systems practiced worldwide. Albizia species is used to treat anxiety, cancer, depression, insomnia, sore throat and to reduce swelling associated with trauma. Isolation of active constituents and pharmacological screening can assist us to find new therapeutically active drugs. The compound (1) 2,2- dimethylvinyl methyl ketone and compound (2) 2,6,10,15,19,23-Hexamethyl-2,6,10,14,18,22-tetracosahexene (C30H50) are isolated from hexane and ethyl acetate fraction of albizia procera belonging to the family mimosoideae. The above isolated Compound (1) is an intermediate to synthesis a number of different types of organic compounds and Compound (2) showed potential hepatoprotective effect against drug induced hepatotoxicity. The structure of compound have been established [1] by IR, 1H NMR, 13C NMR and MASS spectrophotometry.